Financing livestock services in some countries of East and Southern Africa - Anteneh, A. (International Livestock Centre for Africa, 1985)
Examines the financing of livestock services in six East and Southern African countries, describing the contribution of the livestock sector to agricultural output and the size of the recurrent expenditure on livestock services. Compares the composition of expenditures in terms of staff and non-staff categories as well as the sources and methods of financing, including revenues collected from service fees and sale of veterinary requisites. Includes recommendations for improving the adequacy of financing livestock services.